pre-cal

Given that lim x->c f(x)=6 and that lim x->c g(x)= -4, evaluate the following limit. Assume that c is a constant. The x in front of the f is confusing me.
lim [xf(x) + 3 g(x)]^2
x->c

  1. 👍 0
  2. 👎 0
  3. 👁 105
asked by Randy
  1. The x in front of the f is any constant you would put in the equation.

    Example: x->5 5=c
    lim [xf(x) + 3 g(x)]^2
    x->5

    so, [5*6 + 5*(-4)]^2

    You should be able to do the rest.

    1. 👍 0
    2. 👎 0
    posted by John
  2. [c*6 + 3*(-4)]^2 = (6c -12)^2
    = 36c^2 - 144c + 144

    1. 👍 0
    2. 👎 0
    posted by drwls

Respond to this Question

First Name

Your Response

Similar Questions

  1. math

    i need some serious help with limits in pre-calc. here are a few questions that i really do not understand. 1. Evaluate: lim (3x^3-2x^2+5) x--> -1 2. Evaluate: lim [ln(4x+1) x-->2 3. Evaluate: lim[cos(pi x/3)] x-->2 4. Evaluate:

    asked by Dani on July 13, 2010
  2. Calculus Limits

    Question: If lim(f(x)/x)=-5 as x approaches 0, then lim(x^2(f(-1/x^2))) as x approaches infinity is equal to (a) 5 (b) -5 (c) -infinity (d) 1/5 (e) none of these The answer key says (a) 5. So this is what I know: Since

    asked by Anonymous on March 2, 2019
  3. Math-Limits

    How do we evaluate limit of, lim x-> 0 [ln(x+1)/( (2^x) - 1)] I tried using the substitution x+1 = e^k , when x tends to 0 so does k, which gave out, lim k->0 [ k/((2^((e^k) - 1)) -1 ) ] which I simplified into( for the ease of

    asked by Ashley on May 12, 2018
  4. Pre-Cal

    Given that lim x-> f(x)=6 and that lim x-> g(x)= -4, evaluate the following limit. Assume that c is a constant. lim -2f(x) - 12 / g(x). x->. I did -2(6) - (12/-4) -12 - (-3) -12 + 3 -9

    asked by Randy on May 5, 2010
  5. math

    the limit of cuberoot((-3x^3+5x+2)/(x^2-1)) as x approaches 3 is the problem. how could (-3x^3+5x+2) so it would be factored out with denominator? thanks! If you read the answer I gave for the previous question, then you can take

    asked by . on September 3, 2006
  6. calc

    need to find: lim as x -> 0 of 4(e^2x - 1) / (e^x -1) Try splitting the limit for the numerator and denominator lim lim x->0 4(e^2x-1) (4)x->0 (e^2x-1) ______________ = ________________ lim lim x->0 e^X-1 x->0 e^x-1 Next solve for

    asked by brian on September 26, 2006
  7. L'Hopitals Rule

    5) Use the L’Hopital’s method to evaluate the following limits. In each case, indicate what type of limit it is ( 0/0, ∞/∞, or 0∙∞) lim x→2 sin(x^2−4)/(x−2) = lim x→+∞ ln(x−3)/(x−5) = lim x→pi/4

    asked by Jane on December 7, 2014
  8. Math

    Find the limit of the sequence 2ln(1+3n) - ln(4+n^2) What I did: lim as n approach inf of an = 2*lim ln (1+3n)/(4+n^2) = 2 * lim ln (1/n^2 + 3n/n^2) / (4/n^2 + n^2/n^2) = 2 * lim ln (1/n^2 + 3/n) / (4/n^2 + 1) = 2 * lim ln

    asked by Helloo on April 25, 2019
  9. Calculus

    Find the indicated limits. If the limit does not exist, so state, or use the symbol + ∞ or - ∞. f(x) = { 2 - x if x ≤ 3 { -1 + 3x - x^2 if x > 3 a) lim 3+ f(x) x->3 b) lim 3- f(x) x->3 c) lim f(x) x->3 d) lim ∞ f(x) x->3

    asked by Chris on October 9, 2011
  10. Calculus

    Find the indicated limits. If the limit does not exist, so state, or use the symbol + ∞ or - ∞. f(x) = { 2 - x if x ≤ 3 { -1 + 3x - x^2 if x > 3 a) lim 3+ f(x) x->3 b) lim 3- f(x) x->3 c) lim f(x) x->3 d) lim ∞ f(x) x->3

    asked by Blue on October 8, 2011

More Similar Questions